(untitled) (Bulletin KNOB, 2007)
In 1892 Adriaan Willem Weissman (1858-1923) designed the Stedelijk Museum at Paulus Potterstraat in Amsterdam. Hardly ten years later he built the detached town house with picture gallery ’LizzyCottage’, at the corner of Hobbemastraat and Jan Luijkenstraat. In this short period of time his architecture went through fundamental changes: whereas the main form of the museum was based on Dutch architecture of the early seventeenth century, the appearance of Lizzy Cottage is considerably less historicizing. In the last decade of the nineteenth century the work of colleague-architects. among whom H.P. Berlage (1856-1934), Ed. Cuypers (1859-1927) and G. van Arkel (1858-1918) went through a similar development: they abandoned the decorations of the Dutch neo-Renaissance and were looking for a new, more contemporary architecture. From the beginning of his career Weissman did not only present himself as a designer, he also had an extremely facile pen. In the eighties publications started to pour out, which only came to an end with his death in 1923. His articles show that Weissman kept a close track of the architectonic developments and professional literature in Europe and the United States and liked to comment on them. Thanks to his many articles in the journal ‘De Opmerker’ Weissman’s quest for a contemporary architectonic form of expression can be followed in detail during the decade 1892-1902. In succession he took an interest in Dutch architecture of around 1600. Contemporary American architecture (especially H.H. Richardson drew his attention) and contemporary English architecture, notably the Queen Anne Movement. Unmistakably Lizzy Cottage is indebted to English architecture of that period. However, in spite of its name Weissman regarded the house as typically Dutch. For instance, he left out the hall and thus dissociated himself from Ed. Cuypers, who had applied this element in the nearby house Jan Luijkenstraat 2-2A (1898-1899). According to Weissman the hall was only useful in English society, a view he shared with Hermann Muthesius, who had lived in England for a long time. Weissman considered the German architect a kindred spirit; he introduced his ideas - in translation - in the Netherlands. Just as Muthesius, Weissman belongs to the large group of architects with an eclectic, practical bias who did not design from ideological motives. Efficiency was their motto.